Higher prevalence of goitre but not thyroid nodules among the younger age groups in Malaysia: Results of a nationwide study into thyroid disorders - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Ab Wahab, Norasyikin; Sukor, Norlela; Kamaruddin, Nor Azmi (Korean Thyroid Association, 2017)
To determine the prevalence of goitre and thyroid nodule(s) in the Malaysian adult population This is a cross sectional study involving 2259 subjects selected from 5 pre-assigned regions which were representatives of the Malaysian socioeconomic and geographical background. Sixty-nine subjects were excluded due to incomplete data. The prevalences of goitre and thyroid nodule(s) were determined in 2054 subjects who did not report any history of thyroid diseases nor taking any thyroid medications (disease-free population). Hundred thirty-six subjects with known thyroid disorders were analyzed in detail. The presence of goiter or thyroid nodule(s) was determined by trained specialist physicians and positive findings were corroborated by another investigator. The WHO grading of goitre (2014) was used. The hormonal assays and thyroid antibodies were performed using the Architect and Immulite systems respectively. The prevalence of grade 1 and grade 2 goiter were 5.0% and 4.3% respectively. The prevalence of thyroid nodule(s) was only 3.6%. Seventy-two percent of goiters and 68% of thyroid nodule(s) were new findings. The prevalence of goitre and thyroid nodule(s) were higher in females in both the total population (13.2% and 4.6%) and disease-free population (9.3% and 3.3%). Goitre was more prevalent in those aged less than 45 years (12.1% vs 8.0%). Indians had a higher prevalence of grade 2 goitres. The presence of goitre was associated with positive anti-TPO and anti-TG antibodies. Regions located in rural and inland areas had significantly higher prevalence of goitre but not that of thyroid nodule(s). These areas had been shown to suffer from some degree of iodine insufficiency. The prevalence of goitre and thyroid nodule(s) in this population was 9.3% and 3.6%, respectively. Higher prevalence of goitre was observed in females, younger age group and Indians. Higher prevalence of goitre in rural and inland areas may be indicative of iodine insuffficiency.